Handedness in low-birthweight children: Insights in lateralization - Ittyerah, Miriam (Frontiers in Psychology, 2023)
Low-birthweight (LBW) children (n = 96) weighing less than 2.5 kg at birth and normal birthweight (NBW) children (n = 96) from Delhi, India, between the ages of 5 and 12 years were assessed for intelligence with Ravens Colored Progressive Matrices (RCPM), their handedness and hand proficiency for unimanual and bimanual performance. The objective was to know if there is a relation between birthweight and the development of handedness. Compared with NBW children, the LBW group had lower percentile scores for the RCPM. The LBW children were less lateralized than the NBW children in the hand preference test. The LBW children were faster than the NBW for sorting objects with each hand separately, but they were slower in the bimanual envelope task. This indicates a delay in interhemispheric transfer and the development of the corpus callosum that connects the cerebral hemispheres to enable bimanual coordination. In the absence of more direct evidence, hand skill was used as an index of the extent of lateralized control for performance. Findings indicate a relation between birthweight and lateralization in children tested for hand preference.